Management of post-traumatic stress disorder: A protocol for a multiple treatment comparison meta-analysis of randomized controlled trials. Issue 39 (September 2019) - Rehman, Yasir; Sadeghirad, Behnam; Guyatt, Gordon H.; McKinnon, Margaret C.; McCabe, Randi E.; Lanius, Ruth A.; Richardson, Donald J.; Couban, Rachel; Sousa-Dias, Helena; Busse, Jason W.
Abstract: Background: Most systematic reviews have explored the efficacy of treatments on symptoms associated with post-traumatic stress disorder (PTSD), which is a chronic and often disabling condition. Previous network meta-analysis (NMA) had limitations such as focusing on pharmacological or psychotherapies. Our review is aims to explore the relative effectiveness of both pharmacological and psychotherapies and we will establish the differential efficacy of interventions for PTSD in consideration of both symptom reduction and functional recovery. Methods: We will conduct a network meta-analysis of randomized controlled trials evaluating treatment interventions for PTSD. We will systematically search Medline, PILOT, Embase, CINHAL, AMED, Psychinfo, Health Star, DARE and CENTRAL to identify trials that: (1) enroll adult patients with PTSD, and (2) randomize them to alternative interventions or an intervention and a placebo/sham arm. Independent reviewers will screen trials for eligibility, assess risk of bias using a modified Cochrane instrument, and extract data. Our outcomes of interest include PTSD symptom reduction, quality of life, functional recovery, social and occupational impairment, return to work and all-cause drop outs. Results: We will conduct frequentist random-effects network meta-analysis to assess relative effects of competing interventions. We will use a priori hypotheses to explore heterogeneity between studies, and assess the certainty of evidence using the GRADE approach. Conclusion: This network meta-analysis will determine the comparative effectiveness of therapeutic options for PTSD on both symptom reduction and functional recovery. Our results will be helpful to clinicians and patients with PTSD, by providing a high-quality evidence synthesis to guide shared-care decision making.